Elastic Behavior of γ-Li3N under Pressure - Hossain, M. A.; Islam, A. K. M. A. (Journal of Scientific Research, 2011)
The elastic properties of gamma-Li3N have been studied for the first time by first-principles method. Three independent elastic constants, aggregate elastic moduli (B, G, E), Poissons ratio and Debye temperature are calculated as a function of pressure from 37.12 (beta to gamma transition value) to 200 GPa and the implications of the results are discussed. Keywords: Li3N; Gamma-phase; Elastic properties; Debye temperature. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7832 J. Sci. Res. 3 (3), 579-584 (2011)